ANALISA PENGARUH PENGELOLAAN VALUTA ASING TERHADAP POTENSI PENDAPATAN SELISIH KURS - Chairiel Oktaviar (Universitas Mercu Buana, 2017)
Foreign Exchange (FOREX) in any country would be goods or commodities is verytempting because it will bring the benefits of revenue arising from each transaction,however currency also simultaneously contain enough risk frightening when there arefluctuations in the exchange rate very drastic either hike rate or decrease in the exchangerate. Foreign exchange management often does not correspond to the demands and needsof branch operations during takeover for market and the trend does not take into accountfluctuations in the exchange rate would result in losses for the bank. Banks must be goodrhythms urgency of a takeover or a foreign exchange transaction , whether buying orselling bank notes or purchase of traveler checks , since the takeover and resale shouldhave the right timing , the bank is also not allowed to conduct transactions with foreigncurrency exceeding the Net Open Position ( NOP ).